Surveying Orius species (Hemiptera: Anthocoridae) in the South African sugarcane agro-ecosystem as potential biological control agents for Fulmekiola serrata Kobus (Thysanoptera: Thripidae) and other sap sucking pests - Bonte, Jochem; Maes, Sara; Vangansbeke, Dominiek; Cottenie, Ben; Way, Mike; De Clercq, Patrick; Conlong, Des (African Entomology, 2024)
Natural enemy surveys, especially for indigenous anthocorid predators of sugarcane thrips Fulmekiola serrata Kobus, were completed between 2008 and 2013 in and around sugarcane fields in the Mpumalanga and KwaZulu-Natal provinces of South Africa. Four Orius species were recorded during the surveys. First records for South Africa of Orius tantillus (Motchulsky) and Orius naivashae (Poppius) were made, and the presence of Orius thripoborus (Hesse) and Orius brunnescens (Poppius) in the country was confirmed. For each species, habitat and climate preferences are described. Orius thripoborus was the only anthocorid natural enemy which was observed preying on the sugarcane thrips in the field.